Geographic Information Systems Model for Curriculum Management on Cloud Computing in Supply Chain for Higher Education Institution - Artaphon Chansamut (ExcelingTech, 2022)
This article about geographic information systems model for Curriculum management on Cloud Computing in Supply Chain for higher education institution is important for the effectiveness of the model as well as the application in actual work settings. Literature on Cloud Computing in Supply Chain. The objectives of this study are to design and to evaluate geographic information systems model for Curriculum management on Cloud Computing in Supply Chain for higher education institution. The participants were 5 experts in supply chain management, 2 experts in information and technology and 3 experts in Curriculum, totalling 10 experts. The research tool was the questionnaire about geographic information systems model for Curriculum management on Cloud Computing in Supply Chain for higher education institution comprising of eight principal components, namely, Main components, Suppliers, University, Platform as Service, Information exchange, Internet access, Graduate student, Customers. The data were analyzed by using arithmetic mean and standard deviation. The evaluation result from experts agreement geographic information systems model for Curriculum management on Cloud Computing in Supply Chain for higher education institution was a high level and can develop geographic information systems on Cloud Computing in Supply Chain the tasks.